CATEGORY OF POLITENESS IN ENGLISH AND UZBEK PROVERBS («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article research explores the category of politeness in English and Uzbek proverbs, examining the cultural values and societal norms reflected in these expressions of wisdom. Politeness, an essential aspect of human communication, plays a significant role in fostering positive relationships and creating a harmonious social environment. The study analyzes a selection of English and Uzbek proverbs, identifying common themes and unique cultural perspectives on politeness. By examining these proverbs, the research aims to uncover the shared principles and cultural variations in understanding politeness across these languages. This comparative analysis sheds light on the universal recognition of the importance of politeness and its impact on interpersonal dynamics, promoting cross-cultural understanding and appreciation of diverse linguistic and cultural practices.
Keywords: Cross-cultural understanding, interpersonal dynamics, Face, Positive Politeness, Negative Politeness, FTA, off-record, PPS.